The effect of fertilizer P on growth and production of mung bean plants (Phaseolus radiates L.) - Al Machfudz WDP; Agusti Budi Ardhiansyah (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this study is to determine the effect of P fertilizer on the growth and production of green beans plants (Phaseolus radiates L.). This research was carried out on paddy fields in the village Jiken district of reinforcement sidoarjo regency in May 2018 until July 2018. This study used a randomized design of single factor group with 6 threatment and 3 replications so that experimental units were obtained. As for the thretament is the dose of P fertilizer as follows: P1 = 25 kg/ha, P2 = 50 kg/ha, P3 = 75 kg/ha, P4 = 100 kg/ha, P5 = 125 kg/ha, P6 = 150 kg/ha. Parameters observed were plant height, number of leaves, stem diameter, number of pods, number of flowers, number of pods, number of pods, weight of pods, weight of stover, and weight of 100 seeds. The results of the study were than analyzed using analysis of variance or ANOVA and continued by using a 5% method. After the ANOVA test and BNJ 5% showed that the effect of P fertilizer significantly affected the plant height variable at 12 days after planting. While the dosage of P fertilizer gives the best results, namely the variable plant height at P6 threatment with a dose of P fertilizer as much as 150 kg/ha showed the highest average yield of 22,00 and while the threatment of P1 with a dose of P fertilizer as much as 25 kg/ha showed the lowest yield that is equal to 3,61.